From a centralized to a decentralized global economic architecture: An overview - Pradumna B. Rana (Asian Development Bank Institute (ADBI), 2013)
This paper argues that calls for a New Bretton Woods system in the aftermath of the global economic crisis - similar to the remarkable 1944 Bretton Woods conference that led to the establishment of various international economic institutions - are unlikely to be answered. The likely scenario is that the centralized architecture from before the global economic crisis will evolve toward a more decentralized and multilayered global architecture where regional institutions are linked together to a "senior" global organization in a complementary manner by rules and regulations. The paper also highlights the new regional institutions that Asia needs to establish to contribute to this evolving global economic architecture.
Keywords: F02; F13; F33; F53; 330; bretton woods; global economic crisis; international economic institutions; asia; regional institutions; Wirtschaftskrise; Ansteckungseffekt; Regulierung; Internationale Wirtschaftsorganisation; Weltwirtschaftsordnung; Asien; Welt